Poverty and livelihood problems among the scheduled tribes in Kerala-A Study on Attappady - Haseena V.A (Journal of Poverty, Investment and Development, 2015)
The word 'tribe' is generally used for a socially cohesive unit, associated with a territory, the member of which regards them as politically autonomous. Often a tribe possesses a distinct dialect and distinct cultural traits. Tribe can be defined as a “collection of families bearing a common name, speaking a common dialect, occupying or professing to occupy a common territory and is not usually endogamous though originally it might have been so”. According to R.N. Mukherjee, a tribe is that human group, whose members have common interest, territory, language, social law and economic occupation. Scheduled Tribes in India are generally considered to be ‘Adivasis,’ meaning indigenous people or original inhabitants of the country. The tribes have been confined to low status and are often physically and socially isolated instead of being absorbed in the mainstream Hindu population. Psychologically, the Scheduled Tribes often experience passive indifference that may take the form of exclusion from educational opportunities, social participation, and access to their own land. All tribal communities are not alike. They are the products of different historical and social conditions. They belong to different racial stocks and religious backgrounds and speak different dialects. Discrimination against women, occupational differentiation, and emphasis on status and hierarchical social ordering that characterize the predominant mainstream culture are generally absent among the tribal groups. Although Scheduled Tribes are a minority, they constitute about 8.2 % of the total population in India, or 85 million people in absolute number .The tribal population is an integral part of India’s social fabric and has the second largest concentration after that of the African continent.